Teaching from The Immortal Life of Henrietta Lacks: Student perspectives on health disparities and medical ethics. (April 2017) - Dimaano, Christian; Spigner, Clarence
Objective: The Immortal Life of Henrietta Lacks by Rebecca Skloot is an award-winning biography engaging its readers on important topics ranging from race, science and ethics to the social determinants of health. However, the multiple pedagogic impacts of this book on the public health classroom setting have yet to be comprehensively explored. Method: A qualitative, pre/post-test study design assessed the perceptions of 17 Master's of Public Health students on topics of health disparities and medical ethics. A total of 14 students were assigned to an intervention (book-based seminar course; Cohort A) and 3 students acted as the non-intervention group (Cohort B) over a study period of 10 weeks. Results: A thematic analysis uncovered more profound changes in the perceptions of the intervention group. All students were aware of health disparities over the course of the 10-week class; however, significant traction was gained on more complex issues linked to the social determinants of health. Specifically, students in the intervention group showed deeper perceptions about health inequalities with a particular focus on racial disparities. Conclusion: Although graduate students in the public health discipline were well aware of health inequalities, a seminar course surrounding a popular book about Henrietta Lacks afforded students a more concrete understanding for why and how race and racism in health disparities exist.